IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH DI SD N KOTAGEDE 3 YOGYAKARTA TAHUN AJARAN 2016/2017 - Melani Septi Arista Anggraini; Heri Maria Zulfiati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
This study aims to describe the implementation of character education through school culture in SD N Kotagede 3, Umbulharjo Yogyakarta. This research is a descriptive study using a qualitative approach. Subjects of this study consisted of one principal, six teachers, two teachers extracurricular, three students of class IV, V and VI, and the school committee. Selection of research subjects have been with a certain consideration. The experiment was conducted in SD N Kotagede 3, Umbulharjo Yogyakarta. The technique of collecting data using interviews, documentation and observation  moderate  because  the  researchers  only  do  some  of  the  activities  undertaken  by  the speaker.  Data  analysis  techniques  used  during  this  study  using  an  interactive  model  Miles  and Huberman, namely data collection, data reduction, data presentation, and conclusion. The results showed  that  the  implementation  of  character  education  through  a  school  culture  that  is  carried out in SD N Kotagede 3 includes intrakurikuler including 5S, MCC, breakfast, tadarus classical, gymnastics mass, flag ceremony, Thursday pahingan, warning big day, smutlis, waste sorting and go library. In addition intrakurikuler activities, the implementation of character education through school culture in SD N Kotagede 3, Umbulharjo, Yogyakarta is also manifested in extracurricular activities, namely the scouts, TPA, ICT, dance, batik, marching band, gamelan, music, alteltik, karate and qiroah. Character values  that are formed in the implementation of character education through school  culture  held  in  SD  N  Kotagede  3  covers  religious,  disciplined,  responsible,  independent, creative, environmental care, social care, honest, hard work, patriotism, and love to read. Inhibiting factors and support in implementing character education through school culture in SD N Kotagede 3, namely, teachers, students, parents and facilities can be a contributing factor as well as inhibiting the culture of the school, depending on how the responses and action given every component on any activities carried out.